2021
DOI: 10.7189/jogh.11.08003
|View full text |Cite
|
Sign up to set email alerts
|

Trends in complementary feeding practices and caregivers’ feeding knowledge among children aged 6-23 months: Repeated cross-sectional surveys in rural Qinghai China 2012-18

Abstract: Background Appropriate infant and young child feeding is the basis for child survival, growth and development. The aim of this study was to investigate trends in complementary feeding practices and caregivers’ feeding knowledge among children from 2012 to 2018 in Huzhu County, Qinghai Province, China. Methods This study took place during and after a controlled interventional evaluation trial in Qinghai Province, China, which aimed to evaluate the effectiveness of commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
7
0
2
Order By: Relevance
“…Monitoring of health programs and monitoring insights are important tools for adaptive management. For example, authors of an evaluation study on nutrition demonstrated that program monitoring was critically important for understanding program implementation and adherence trends which led to strategic changes to the intervention over time 31 . Monitoring also plays a crucial role in providing stakeholders with an overview of a program's progress towards its targets.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of health programs and monitoring insights are important tools for adaptive management. For example, authors of an evaluation study on nutrition demonstrated that program monitoring was critically important for understanding program implementation and adherence trends which led to strategic changes to the intervention over time 31 . Monitoring also plays a crucial role in providing stakeholders with an overview of a program's progress towards its targets.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini menjadi salah satu penyebab banyaknya status gizi anak yang tidak mengalami peningkatan setelah diberikan tata laksana oleh bidan. Penelitian Wu dkk 15 menemukan bahwa pemberian informasi pada orang tua atau pengasuh melalui berbagai media, seperti internet dan telefon genggam dapat menjadi sarana tambahan dalam memberikan konseling dan informasi pada orang tua dan pengasuh.…”
Section: Pembahasanunclassified
“…Existing knowledge uncovers that most caregivers may demonstrate satisfactory feeding practices when at health facilities due to the closest support, nutritional education, and guidance from healthcare professionals [ 3 ]. However, the continuum of appropriate feeding of under-five children within the recommended dietary adequacy and diversifications has been an utmost challenge among caregivers to maintain a smooth feeding transition from health facilities to home and improve children’s health outcomes [ 4 ]. Unfortunately, it appears that comprehensive follow-ups and support at their homes are not widely available for many caregivers, particularly in the developing world [ 5 ].…”
Section: Introductionmentioning
confidence: 99%